Unusual coexistence: branchial cleft cyst harboring papillary thyroid carcinoma with lymph node metastasis — a rare case report and clinical insights - Wang, Wei-Tao; Ni, Xi-Hao; Gu, Yong-Xue; An, Ran; Wang, Chang-Liang; Zhang, Jun (Frontiers in Oncology, 2024)
Background The simultaneous occurrence of Branchial Cleft Cyst (BCC) and Papillary Thyroid Carcinoma (PTC) represents an unusual malignant tumor, with cases featuring associated lymph node metastasis being particularly rare. This combination underscores an increased potential for metastasis, and the assessment of neck masses, particularly on the lateral aspect, may inadvertently overlook the scrutiny of the thyroid. Therefore, healthcare providers should exercise vigilance, especially in patients over the age of 40, regarding the potential for neck masses to signify metastasis from thyroid malignancies. Currently, surgical intervention stands as the primary effective curative method, while the postoperative administration of radioactive iodine therapy remains a topic of ongoing debate. Case report In the presented case, a 48-year-old male patient with a right neck mass underwent surgical intervention. The procedure included the excision of the right neck mass, unilateral thyroidectomy with isthmus resection, and functional neck lymph node dissection under tracheal intubation and general anesthesia. Postoperative pathology findings revealed the coexistence of a BCC with metastatic PTC in the right neck mass, as well as papillary carcinoma in the right thyroid lobe. Lymph node metastasis was observed in the central and levels III of the right neck. Conclusion The rare amalgamation of a BCC with PTC and concurrent lymph node metastasis underscores the invasive nature of this malignancy. Healthcare professionals should be well-acquainted with its clinical presentation, pathological characteristics, and diagnostic criteria. A multidisciplinary approach is strongly recommended to enhance patient outcomes.